Validity and Reliability of English Summative Test for Senior High School - Aris Sugianto (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2017)
This study aims to analyze statistically the validity and reliability of English summative test for the second semester of the tenth graders of SMAN 2 Palangka Raya in academic year 2015/2016. The writer used descriptive quantitative approach to find the result. In analyzing the validity, the writer used Point-biserial correlation formula, while to analyze the reliability, the writer used K-R20 formula. The validity was analyzed based test item, and the validity of whole test was determined based on the percentage of all valid items. The result was that the English summative test was valid and reliable. Specifically, from 50 items of questions, 32 items (64%) were valid and 18 items (36%) were invalid. Interpreted from the 64% of valid items, so overall the summative test was valid in substantial level. The summative test was also reliable. The coefficient of reliability was .907. Therefore, the reliability was in the level of excellent reliability.